2003
DOI: 10.1111/1540-627x.00077
|View full text |Cite
|
Sign up to set email alerts
|

Export Marketing Performance: A Study of Thailand Firms

Abstract: This study identifies the statistically significant predictors of export marketing performance for Thai export firms. The export performance scale developed by Cavusgil and Zou (1994) is refined and tested in Thailand. A set of potential determinants of export marketing performance is considered and the unit of analysis is the individual product-market export venture. The data for this study were collected from a mail questionnaire survey of 1,000 Thai export firms in Thailand. The sample consisted of 151 smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
0
13

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 81 publications
(105 citation statements)
references
References 18 publications
4
88
0
13
Order By: Relevance
“…The reason being is that when these conditions are prevalent they will necessitate the need for the firm to have a partner that has a reliable distribution network, local manufacturing and local market knowledge. Otherwise distribution and successful market penetration will be next to impossible and many studies have already identified the importance of distribution access for international marketing success (Julian, 2003;Karakaya, 1993;Makino & Delios, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason being is that when these conditions are prevalent they will necessitate the need for the firm to have a partner that has a reliable distribution network, local manufacturing and local market knowledge. Otherwise distribution and successful market penetration will be next to impossible and many studies have already identified the importance of distribution access for international marketing success (Julian, 2003;Karakaya, 1993;Makino & Delios, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Venture management characteristics as a barrier to internationalization includes such issues as managerial indifference towards the value of internationalization, management emphasis on developing domestic markets, insufficient personnel to manage international trade activity and a lack of capacity for international expansion (Julian, 2003). As far as having insufficient personnel to manage international trade activity is concerned, the international business literature suggests that small firms have a general problem with inadequate expertise and skills at managerial, supervisory and production employees level (Holmund & Kock, 1998).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, this study has developed an objective measure of IJV marketing performance that is highly correlated with a subjective measure of marketing performance. Thereby, leading to the conclusion that the objective measure developed for this study could be used by other researchers interested in examining IJV and other market entry mode's marketing performance (see Julian, 2003).…”
Section: Discussion Implications and Conclusionmentioning
confidence: 99%
“…İşletmelerin uluslararası pazarlara açılmaları, bu pazarlarda başarılı olmaları ve başarılarının sürdürülebilirliği ihracat performans düzeylerine bağlı olabilecektir. İhracat performansı, literatürde yer alan pek çok çalışmada (Fenwick, Amine, 1979;Bilkey, 1982;Madsen, 1989;Walters, Samiee, 1990;Kaynak, Kuan, 1993;De Luz, 1993;Okoroafo, Russow, 1993;Çavuşgil, Zou, 1994;Naidu, Prasad, 1994;Thirkell, Dau, 1998;Hoang, 1998;Katsikeas vd., 2000;Shoham, 2000;Baldauf vd., 2000;Robertson, Chetty, 2000;Jullian, 2003) belirlenmiş objektif ve subjektif ölçüm kriterleri ile ölçülebilmektedir. Objektif ölçüm kriterleri sayısal veriler ile ifade edilir ve ihracat oranı, ihracat kârları, ihracat satışları gibi finansal ölçüm kriterlerini içerir (Jullian, 2003: 213-215).…”
Section: Ori̇ji̇nal Tasarim üReti̇mi̇ İle Ori̇ji̇nal Marka Ve İhracat Perfounclassified